-2(v+3)=-5v-18

Simple and best practice solution for -2(v+3)=-5v-18 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for -2(v+3)=-5v-18 equation:



-2(v+3)=-5v-18
We move all terms to the left:
-2(v+3)-(-5v-18)=0
We multiply parentheses
-2v-(-5v-18)-6=0
We get rid of parentheses
-2v+5v+18-6=0
We add all the numbers together, and all the variables
3v+12=0
We move all terms containing v to the left, all other terms to the right
3v=-12
v=-12/3
v=-4

See similar equations:

| y/7+3=34 | | 11(r+12)=11 | | 3(-3-8x)-1=-202 | | x/5+14=1 | | 3(x-6)+2x=9x+7 | | -17.73+8.1t=12.33+9.9t | | 5−5x+6x−36=−24−17x+17x+24 | | k/7.8+41.7=15.4 | | 20-16b=4+9-17b | | 5000+0.8x=6800 | | 2m=m+11 | | 4+15z=-13+14z | | 2x+8=17-x | | 14(w+1)=14 | | 5w+10=55 | | -7.5x+0.51=-5.49−7.5x+0.51=−5.49 | | 4x-7+8=16 | | -7-3b=8b+7-4b | | 8(7+6k)+3k=158 | | 10-10y=-8y | | 16x−16x+x= | | −7.5x+0.51=−5.49 | | 5x+7+2x+22=x+5 | | 2.75x=25/32 | | 31=-8t-9 | | -9-3h=6h | | 23x+17=3x+117 | | x–7=-9 | | -8+6v=8v+10 | | 3m+2-10m=-4-4m | | -2/3t=9 | | 3x(11x-13=9) |

Equations solver categories